The Relationship between Osteoarthritis and Osteoporosis in Patients with Primary Generalized Osteoarthritis - Aigul ZHOLDOSHOVA; Peyman YALÇIN (Archives of Rheumatology, 2013)
Objectives: This study aims to examine the relationship between primary generalized osteoarthritis (OA) and bone mineral density (BMD) and to investigate whether OA patients have a higher BMD value than healthy individuals. Patients and methods: The study population consisted of 80 postmenopausal female patients (mean age 58.95±4.63 years) who suffered from hand OA with Heberden's nodes, while the control group consisted of 80 postmenopausal female patients (mean age 57.62±5.39) without symptomatic OA and Heberden's nodes. The patients were age-matched. Blood biochemistry, thyroid function tests and bone turnover markers (serum calcium, phosphorus, alkaline phosphatase, osteocalcin, and urine deoxypyridinoline) and 25-hydroxyvitamin D3 [25(OH)D3] levels of the participants were measured. A comparison was made between the two groups with regard to BMD levels, lateral thoracolumbar X-rays, and anteroposterior radiographs of the pelvis, knees, and hands. The evaluation of the radiographs was based on the Kellgren-Lawrence scale. The lumbar and femoral BMD levels in both groups were measured in g/cm2 with dual-energy X-ray absorptiometry. Results: The 25(OH)D3 value of the OA group was significantly higher than the control group, indicating a statistically significant difference. The lumbar spine BMD levels were statistically higher in the control group compared with the OA group, however, there were no significant differences in the hip BMD values and lumbar spine T scores between the groups. Conclusion: Our study results suggest that primary generalized OA is not protective against osteoporosis.